2001
DOI: 10.1128/iai.69.4.2130-2136.2001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines Expressing a Fusion Product of Outer Surface Proteins A and C fromBorrelia burgdorferiInduce Protective Antibodies Suitable for Prophylaxis but Not for Resolution of Lyme Disease

Abstract: DNA vaccines encoding the outer surface protein A (OspA) ofBorrelia burgdorferi have been shown to induce protective humoral responses capable of preventing but not curing infection in mice. Subsequent studies showed that an established infection or disease could be resolved by passive transfer of antibodies to OspC. In the present study, DNA vaccines encoding either the OspC antigen alone or fused to OspA and under the transcriptional control of the human elongation factor 1α promoter were evaluated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…5B). In these settings, the potential of P 3 CSK 4 to restore the antigenicity of MDP-OspA in vitro was even higher than that observed with Lip-OspA, which contains palmitoylated chains covalently linked to its N-terminal cystein [21].…”
Section: Blpa Bearing At Least Two Ester-bonded Palmitoylated Side Chmentioning
confidence: 86%
See 4 more Smart Citations
“…5B). In these settings, the potential of P 3 CSK 4 to restore the antigenicity of MDP-OspA in vitro was even higher than that observed with Lip-OspA, which contains palmitoylated chains covalently linked to its N-terminal cystein [21].…”
Section: Blpa Bearing At Least Two Ester-bonded Palmitoylated Side Chmentioning
confidence: 86%
“…Previous studies have shown that the immunogenicity of OspA critically depends on its lipidation and that in the absence of adjuvant, only the lipidated derivative, LipOspA, but not the methionine/aspartic acid/proline derivative, MDP-OspA, induces protective antibodies in vivo [20][21][22]. We therefore cultured CFSE-labeled CD4 + T lymphocytes, enriched from PBL of healthy donors, with autologous DC in the presence of MDP-OspA and BLpA and assessed T cell proliferation after 5 days.…”
Section: Blpa Bearing At Least Two Ester-bonded Palmitoylated Side Chmentioning
confidence: 99%
See 3 more Smart Citations